Performance of Reinforced Concrete Structures With The Effect Of Door And Window Holes Nonlinear Static Pushover Method - Silvi, Ni Putu; Partama, I Gusti Ngurah Eka; Astariani, Ni Kadek; Sudika, I Gusti Made (Jurnal Ilmiah Teknik Sipil; Vol 27 No 2 (2023): Jurnal Ilmiah Teknik Sipil, Vol. 27 No. 2, September 2023, 2023)
Bricks are generally used as infilled walls or as room dividers in reinforced concrete structural frames. In structural modeling, brick walls are generally modeled as a load. But in reality, infilled walls contribute significantly to the framework of reinforced concrete structures. For this reason, it is necessary to include a wall model in the modeling. In this analysis, 3 models have been made, namely Model M1 is a model without infilling walls (open frame), model M2 is Fully Infilled Wall Frame and model M3 is Fully Infilled Wall Frame with door openings 24.8% and windows 41.6%. The purpose of this study was to determine the performance of reinforced concrete structures with and without the influence of door and window holes in the walls due to lateral loads. The analytical method used is Pushover nonlinear static method. The results showed that the open frame model with the IO (Immediate Occupancy) performance level has the ability to accept smaller lateral loads of 32.77% and 31.31% respectively against the Fully Infilled Wall Frame model and the Fully Infilled Wall Frame model with openings doors 24.8% and windows 41.6% with LS (Life Safety) performance levels due to earthquake loads in the X and Y directions.